ONLINE SHOPPING: ANALYSIS OF THE INFLUENCE OF ETHNOCENTRISM ON PURCHASE INTENTION IN LOCAL COSMETICS - Budiarti, Raden Rara Arifah Mulyo; Simanjuntak, Megawati; Nurhayati, Popong (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
The rapid development of E-Commerce in the current digital era offers various available products and provides greater opportunities for consumers to choose and determine which products to buy. The purpose of this study was to analyze the demographic segmentation of local cosmetic products online consumers and the effect of ethnocentrism on purchase intention in local cosmetics through online shopping. The sampling technique used was non-probability sampling with a convenience sampling method. This study involved a sample of 210 respondents, dominated by women in the age range of 17-24 years, college graduates, unmarried, and have jobs as employees with an income of IDR 5,000,000 – IDR 10,000,000 per month. The research was using the SEM-LISREL analysis tool. The results showed that the ethnocentrism variable had a positive and significant effect on consumer purchase intention. The variables of cultural openness, patriotism, conservatism, and collectivism have a positive and significant effect on ethnocentrism and have a significant indirect effect on purchase intention in local cosmetics through ethnocentrism as an intervening variable. A strategy that can be applied by the company to increase purchase intention of local cosmetics through ethnocentrism is to educate consumers related to Indonesian cultural heritage which is applied to local cosmetics.